RANCANG BANGUN MEDIA BELAJAR FISIKA DASAR UNTUK MAHASISWA BERBASIS ANDROID - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
The design of basic physics aims to assist students in understanding the lessons of physics for students in particular and the general public .. This design contains basic formulas of physics, exercise problems and cases that run with the Android operating system designed specifically for smartphones and tablets, and can be done in offline, so users are not required to connect to the internet to use it. Rapid Application Design method is very well used to solve the problem of misunderstanding between users and analysts arising from the user is unable to clearly define their needs. And the analysis using Unified Modeling Language method used to perform specifications, visualization, construction, and documentation artifact a software system